Plan estratégico para el fortalecimiento de la gestión de la planta purificadora Agua Los Ríos, cantón Montalvo, provincia Los Ríos, período 2023-2027 - Guaman Estrada, Lady Patricia (2024)
The main objective of this titling work was to develop a strategic plan aimed at strengthening the management of the "Agua de los Ríos" purification plant, located in the Montalvo Canton, in the Los Ríos province, covering the period between 2023 and 2027. The fundamental purpose of this plan is to establish a series of administrative strategies that would effectively promote the performance of the plant. The methodology adopted to carry out this project was based on carrying out an exhaustive analysis, both internal and external, using approaches such as the SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) and the PESTEL analysis (Political, Economic, Social, Technological and Environmental). These analyzes provided a detailed view of the situation in which the plant found itself. In addition, a qualitative approach was combined through the use of various matrices and analyses, together with surveys aimed at both the company's employees and its customers.